Impact of anesthetic strategy on outcomes for patients with acute basilar artery occlusion undergoing mechanical thrombectomy. (3rd November 2021) - Li, Fengli; Wan, Junfang; Song, Jiaxing; Yuan, Junjie; Kong, Weilin; Huang, Jiacheng; Luo, Weidong; Wu, Deping; Li, Linyu; Chen, Luming; Zhao, Chenghao; Chen, Jin; et al.
Abstract : Background: The best anesthetic management strategy for patients with acute large vessel occlusion treated with mechanical thrombectomy (MT) remains uncertain. Most studies have focused on anterior–circulation stroke caused by large artery occlusion. Nevertheless, limited data are available on the appropriate choice of anesthetic for acute basilar artery occlusion (BAO). We aimed to investigate the effect of anesthetic method on clinical outcomes in patients with BAO undergoing MT. Methods: Patients undergoing MT for acute BAO in the BASILAR registry (Acute Basilar Artery Occlusion Study) were included. We divided patients into three groups according to the anesthetic technique used during MT: general anesthesia (GA), local anesthesia (LA), and conscious sedation (CS). Propensity score matching was performed to achieve baseline balance. Results: 639 patients were included. GA was used in 257 patients (40.2%), LA was used in 250 patients (39.1%), and CS was used in 132 patients (20.7%). After 1:1 matching, favorable outcome, mortality, and hemorrhagic transformation rates, as well as modified Rankin Scale (mRS) score at 90 days, did not differ between the GA, LA, and CS groups. Conclusions: The choice of anesthetic strategy, GA, LA, or CS, did not affect the clinical outcomes of patients with acute BAO treated with MT in the BASILAR registry.